EKSPLORASI HAMBATAN KEPATUHAN PENGOBATAN PASIEN DIABETES MELITUS DI PUSKESMAS: STUDI KUALITATIF - Alfian, Riza; Fawwazi, Muhammad Hafizh Abiyyu Fathin; Faqih, Muhammad; Adikusuma, Wirawan (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Medication adherence is a crucial factor in the successful management of diabetes mellitus, yet many studies show that adherence remains low and is shaped by multidimensional influences. This study aimed to explore barriers to medication adherence among patients with diabetes mellitus in primary health centers (Puskesmas) using the WHO five-domain adherence framework. A qualitative descriptive-exploratory design was applied. Data were collected through in-depth interviews with ten patients undergoing routine treatment at Puskesmas in Banjarmasin City, recruited through purposive sampling. Thematic analysis was performed guided by the WHO adherence model. Five major themes emerged. Social and economic factors included limited transportation costs, distance to the health center, and lack of family support. Health system and provider factors involved brief consultations, insufficient patient education, and long queues. Condition-related factors comprised the absence of immediate symptoms, fatigue from chronic illness, comorbidities, and psychological distress. Therapy-related factors included complex regimens, side effects, and discontinuation of therapy without consultation. Patient-related factors were characterized by forgetfulness, reliance on alternative medicine, fluctuating motivation, and feelings of boredom. These findings highlight that adherence barriers are multidimensional and result from the interaction of individual, social, and system-level determinants. Addressing adherence requires holistic and continuous interventions at the primary care level, with emphasis on patient education, family involvement, and strengthening the role of healthcare providers.